2020
DOI: 10.1111/ijpo.12704
|View full text |Cite
|
Sign up to set email alerts
|

Associations of DXA‐measured abdominal adiposity with cardio‐metabolic risk and related markers in early adolescence in Project Viva

Abstract: SummaryBackgroundIncreased visceral adipose tissue (VAT) precedes development of insulin resistance and dyslipidemia in adults. The associations of abdominal adiposity derived from dual‐energy X‐ray absorptiometry (DXA), including VAT, subcutaneous abdominal adipose tissue (SAAT) and total abdominal adipose tissue (TAAT) with cardio‐metabolic risk in adolescents are understudied.ObjectivesWe examined the cross‐sectional associations of DXA‐measured abdominal adiposity with cardio‐metabolic risk and related mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Accrual of central adiposity, particularly visceral adipose tissue (VAT), is associated with adverse cardiometabolic health and predicts atherogenic dyslipidemia and type 2 diabetes in adults, independent of BMI (1,2). In adolescents, cross‐sectional studies have shown associations of higher VAT with markers of cardiometabolic risk, such as higher triglycerides (TG) and insulin resistance (3), lower adiponectin and higher leptin (4), and metabolic syndrome (5). In the Framingham Heart Study Third Generation adult cohort, greater computed tomography (CT)‐measured changes in VAT and subcutaneous abdominal adipose tissue (SAAT) were associated with increased incidence of hypertension, hypertriglyceridemia, and metabolic syndrome, as well as adverse changes in cardiovascular disease risk factors, even after accounting for BMI change, waist circumference (WC) change, or baseline abdominal adipose tissue (6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accrual of central adiposity, particularly visceral adipose tissue (VAT), is associated with adverse cardiometabolic health and predicts atherogenic dyslipidemia and type 2 diabetes in adults, independent of BMI (1,2). In adolescents, cross‐sectional studies have shown associations of higher VAT with markers of cardiometabolic risk, such as higher triglycerides (TG) and insulin resistance (3), lower adiponectin and higher leptin (4), and metabolic syndrome (5). In the Framingham Heart Study Third Generation adult cohort, greater computed tomography (CT)‐measured changes in VAT and subcutaneous abdominal adipose tissue (SAAT) were associated with increased incidence of hypertension, hypertriglyceridemia, and metabolic syndrome, as well as adverse changes in cardiovascular disease risk factors, even after accounting for BMI change, waist circumference (WC) change, or baseline abdominal adipose tissue (6).…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported on cross‐sectional associations of DXA‐measured abdominal adiposity with cardiometabolic risk in early adolescence, showing that greater abdominal adiposity, independent of BMI, was associated with higher cardiometabolic risk (4). In this study, we expand on earlier findings using our longitudinal cohort to examine and compare the associations of indirect and direct measures of central adiposity gain from midchildhood (age 7‐10 years) to early adolescence (age 12‐15 years) with cardiometabolic health markers in early adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…DXA has been increasingly used in the measure of whole‐body and centrally‐located adiposity in children 23 . In our analyses, the association between lower maternal insulin sensitivity and greater central adiposity was specifically captured by the truncal fat percentage estimated by DXA.…”
Section: Discussionmentioning
confidence: 91%
“…22 DXA has been increasingly used in the measure of whole-body and centrally-located adiposity in children. 23 In our analyses, the association between lower maternal insulin sensitivity and greater central adiposity was specifically captured by the truncal fat percentage estimated by DXA. The ability to measure body composition via DXA also allowed us to observe that higher maternal insulin secretion was specifically associated with greater lean mass, but no other anthropometric measures or DXA estimates, supporting the value of detailed body composition evaluation to untangle early determinants of growth and adiposity.…”
Section: Key Resultsmentioning
confidence: 99%
“…Additionally, studies in adults and children have found body fat thresholds by air displacement plethysmography to be lower than those established by BMI or WC to define risk ( 42 ). In adolescents, visceral adiposity as measured by DXA was found to be associated with insulin resistance independent of BMI ( 43 ). To our knowledge no longitudinal studies exist evaluating the ability of more advanced measures of body fat measurement to predict future insulin resistance.…”
Section: Advanced Measurements Of Adipositymentioning
confidence: 99%